Advancing One Health security through animal waste surveillance and wildmeat value chains - Patel, Ekta (World Organisation for Animal Health, 2025)
Global health security depends not only on hospitals and laboratories but also on how societies produce, trade and consume animals. With 75% of emerging diseases originating in animals, strengthening animal health systems is critical to preventing spillover events such as Ebola, Rift Valley fever (RVF) or avian influenza. Within a One Health framework, which integrates human, animal and environmental health, animal health acts as the first line of defence, bridging global security priorities with local livelihood realities. This article explores two emerging pathways: animal waste surveillance and underrepresented threats of wildmeat value chains. Studies led by the International Livestock Research Institute (ILRI) demonstrate how abattoir waste can serve as low-cost, scalable surveillance tools, generating early warning for zoonotic threats and antimicrobial resistance. Leveraging tools such as genomics, the case study on RVF shows how genomic and ecological monitoring in livestock reveal patterns that allow preventive action before outbreaks escalate. Equally, research on wildmeat trade in East Africa highlights how informal value chains amplify risks by lacking regulation and protective practices, while being sustained by cultural and economic necessity. Addressing these risks requires community engagement and context-sensitive alternatives rather than criminalisation. Together, these insights demonstrate that advancing animal health systems is not simply a technical upgrade but a strategic investment in One Health security and global stability.